A 3D Analogue of Phenyllithium: Solution‐Phase, Solid‐State, and Computational Study of the Lithiacarborane [Li−CB11H11]−. (11th November 2019) - Dontha, Rakesh; Zhu, Tian‐Cheng; Shen, Yunjun; Wörle, Michael; Hong, Xin; Duttwyler, Simon
Abstract: The lithiacarborane [Li−CB11 H11 ] − plays a central role in carborane chemistry, as it is a key intermediate to achieve the selective functionalization of the monocarba‐ closo ‐dodecaborate [CB11 H12 ] − for applications in various fields. Also, it is an organometallic species of fundamental interest because it represents a 3D analogue of phenyllithium featuring an exo C−Li bond in addition to the delocalized negative endo charge of the spherical cluster. For the first time, the elusive and highly reactive endo/exo formal dianion [CB11 H11 ] 2− has been isolated as its lithiate as well as zincate in pure form and fully characterized. DFT calculations corroborate the experimental findings and underscore the remarkably high reactivity of the lithiacarborane. Subsequent derivatizations demonstrate the relevance of its initial clean formation. Abstract : Analogische 3D‐Erweiterung : Das Lithiacarboran [Li‐CB11 H11 ] − spielt eine zentrale Rolle in der Carboranchemie und ist von grundlegendem Interesse, da es ein 3D‐Analogon von Phenyllithium mit einer exo ‐C‐Li‐Bindung sowie einer sphärisch delokalisierten negativen endo ‐Ladung darstellt. Die Isolierung in hoher Ausbeute sowie strukturelle Charakterisierung des Lithiats und Zinkats werden zusammen mit DFT‐Rechnungen präsentiert.